Photoinduced Cascade Reaction of Tertiary Amines with Sulfonyl Azides: Synthesis of Amidine Derivatives. Issue 15 (1st July 2019) - Ding, Rui; Chen, Hui; Xu, Yan‐Li; Tang, Hai‐Tao; Chen, Yan‐Yan; Pan, Ying‐Ming
Abstract: A metal‐free cascade reaction of tertiary amines with sulfonyl azides promoted by acridinium salts under blue light irradiation was developed and provided amidine derivatives in moderate to good yields. Enamine was generated from tertiary amine via single‐electron transfer promoted by acridinium salts, and the following [3+2] cyclization with sulfonyl azide and CH2 N2 release afforded the desired products. Abstract :